2021
DOI: 10.1108/jpbm-12-2020-3260
|View full text |Cite
|
Sign up to set email alerts
|

“Standing out” and “fitting in”: understanding inspiration value of masstige in an emerging market context

Abstract: Purpose This study aims to investigate the role of middle-class consumers’ need for uniqueness (CNFU), consumer susceptibility to interpersonal influence (CSII), inspiration and behavioral intentions toward masstige products. Specifically, this study examines the differential effects of CNFU dimensions, the underlying mechanism of consumer inspiration and the moderating role of CSII in the purchase intentions toward masstige products. Design/methodology/approach Two studies were carried out to test the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 70 publications
(130 reference statements)
1
21
0
Order By: Relevance
“…Besides, they are also different from luxury in the sense that quality is inherent with traditional luxuries whereas masstige needs to explicitly communicate their quality quotient (Kapferer et al, 2014). Further, studies (Kapferer, 2015; Paul, 2019) indicate that traditional luxury stands for heritage, family name and country of origin whereas masstige express self‐identity through upmarket feeling (Das et al, 2021).…”
Section: Literature Foundationmentioning
confidence: 99%
“…Besides, they are also different from luxury in the sense that quality is inherent with traditional luxuries whereas masstige needs to explicitly communicate their quality quotient (Kapferer et al, 2014). Further, studies (Kapferer, 2015; Paul, 2019) indicate that traditional luxury stands for heritage, family name and country of origin whereas masstige express self‐identity through upmarket feeling (Das et al, 2021).…”
Section: Literature Foundationmentioning
confidence: 99%
“…, 2021). Das et al. (2021) found that interpersonal influence moderated the relationship between need for uniqueness and inspiration for masstige.…”
Section: Literature Overview and Research Hypothesesmentioning
confidence: 96%
“…It is important to note that what consumers perceive to be luxury ranged from traditional luxury to masstige to nontraditional luxury brands (Kowalczyk and Mitchell, 2021;Shin et al, 2021). Das et al (2021) found that interpersonal influence moderated the relationship between need for uniqueness and inspiration for masstige. Thus, it is reasonable that reference group influence can impact both luxury and counterfeit luxury products.…”
Section: Role Of Interpersonal Influencementioning
confidence: 99%
“…How will luxury customers react when their favorite brand becomes accessible to more people? Although the literature is recently focusing on this topic (Das, Saha & Balaji, 2021; Das, Saha and Roy, 2021; Shahid & Paul, 2021), a gap still exists that this study intends to cover as there is still no empirical exploration of how masstige campaigns on social media influence followers and customers (Dash et al., 2021; Joshi & Garg, 2021; Kumar et al., 2021). Additionally, this paper discusses the influence of masstige strategies on attitude toward the brand, and we ground our research on the well‐established attitude toward the brand concept (Mitchell & Olson, 1981; Spears & Singh, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…How will luxury customers react when their favorite brand becomes accessible to more people? Although the literature is recently focusing on this topic (Das, Saha & Balaji, 2021;Das, Saha and Roy, 2021;Shahid & Paul, 2021), a gap still exists that this study intends to cover as there is still no empirical exploration of how masstige campaigns on social media influence followers and cus-…”
mentioning
confidence: 99%